The Level of Responsible Tourism Among Millennials and Generation Z in the Sustainability of the Cetho Temple Tourist Destination - Afrilia Elizabet Sagala; Denny Asmara (Jayapangus Press, 2026)
This study aims to investigates the determinants of responsible tourism behavior among Millennial and Generation Z visitors to Cetho Temple, a cultural and spiritual heritage site in Indonesia. Employing a mixed-methods approach, data were collected from 400 survey respondents and through in-depth interviews with tourists, destination managers, and local stakeholders. Quantitative analysis using SmartPLS 4 reveals that technology (T = 4.842; p < 0.001) and governance & policy (T = 3.657; p < 0.001) significantly influence responsible tourism practices. Social factors exert a marginal yet notable impact (p = 0.045), highlighting the role of peer and community influence. In contrast, educational, economic, environmental, and behavioral intent variables were not statistically significant. Qualitative insights corroborate these findings: Millennials tend to acquire responsible tourism values through formal education, while Gen Z relies more on social media. Despite its potential, technology remains underutilized by destination managers. The study recommends strengthening digital transformation and educational initiatives that integrate diverse sustainable tourism models, such as wellness, heritage, and community-based tourism, to foster long-term sustainability and responsible visitor behavior at heritage sites like Cetho Temple.